The secretary and her boss (London Video Arts, 1977)
This video demonstrates how important the office partnership is by looking at the administrative, human, social and personal skills needed to build a team. It includes the mail, appointments and filing, visitors, telephone calls and dictation procedures
Part 1. Try to see it my way - Part 2. We can work it out
APD 002162
Keywords: Secretaries